Effects of Priming Discriminated Experiences on Emotion Recognition Among Asian Americans - Chang, Sophia; Kang, Sun-Mee (Frontiers in Psychology, 2022)
This study explored the priming effects of discriminated experiences on emotion recognition accuracy of Asian Americans. We hypothesized that when Asian Americans were reminded of discriminated experiences due to their race, they would detect subtle negative emotional expressions on White faces more accurately than Asian Americans who were primed with a neutral topic would. This priming effect was not expected to emerge in detecting negative facial expressions on Asian faces. To test this hypothesis, one hundred-eight participants were randomly assigned to one of two conditions: write about their experiences with racial discrimination (experimental) or write about a neutral topic (control). Then, they were given an emotion recognition test consisting of White and Asian faces. The current study found a significant interaction effect of priming condition by target race. When Asian Americans were reminded of discriminated experiences, they displayed a heightened sensitivity to negative emotional expressions on White faces, but not to the negative expressions on Asian faces. The implications of these findings were discussed.